Myths of Breastfeeding Regarding Mothers’ Diet - AKRAM, AMNA; MAHMOOD, RASHID; SAJID, MUHAMMAD (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To identify myths which are common in our local setup and are the main cause of hindrance in exclusive breastfeeding. Methods: A cross-sectional survey was done at outdoor patient department of Sir Ganga Ram Hospital Lahore from October 2016 to December 2016 with the sample size of 174 women and open ended questions were asked. Results: Among 174 responders, mean age of the patients in this study was 27.8 years, with majority (86.3%) having their education level below matric, and from lower socioeconomic status (83%). Among them, 99 (56.9%) of the mothers were of the opinion to start mother feed immediately after delivery. Furthermore, 130 (74%) mothers think that milk, fruit, and meat are good choice of food.150 (86%) had the opinion and knowledge about thanda food. Conclusion: Numerous myths are circulating among mothers related to food intake with various health issues in baby. Mothers still believe in avoidance of various foods in their diet to avoid problems in baby like colic, constipation and pneumonia.